Topology modeling and analysis of emergency communications network - Wei WANG; Wen-hong ZHAO (Tongxin xuebao)
The construction method,throughput and related properties about the topology model of emergency communication networks were discussed.Firstly,the topology modeling method was presented by three steps,such as the constructions of backbone network,access network and station network.Then,the capacity of network model was analyzed in conditions of arbitrary networks and random networks.At last,some topology properties were discussed,including the shortest path,node degree,rich club,betweenness centrality,current flow centrality,eccentricity and closeness vitality.The experiment results show that the proposed modeling method is steady and applicable to the emergency communication.